2013
DOI: 10.1111/ped.12183
|View full text |Cite
|
Sign up to set email alerts
|

Individual and familial factors associated with metabolic control in children with type 1 diabetes

Abstract: Multiple individual and family-level factors are associated with metabolic control. These data may aid in identification of diabetic children and adolescents who have a higher risk of poor metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
1
13
1
2
Order By: Relevance
“…Professional fathers have children with good glycemic control. Those findings are consistent with previous studies using the same method of our data collection, which have also proved that lower socioeconomic status which mainly results from unemployment of parents is related with higher HbA1c [12][13][14][15]. In contrast and according to the results of this study, neither mothers' educational level nor their occupational status have shown significant influence on their children glycemic control.…”
Section: Discussioncontrasting
confidence: 36%
See 2 more Smart Citations
“…Professional fathers have children with good glycemic control. Those findings are consistent with previous studies using the same method of our data collection, which have also proved that lower socioeconomic status which mainly results from unemployment of parents is related with higher HbA1c [12][13][14][15]. In contrast and according to the results of this study, neither mothers' educational level nor their occupational status have shown significant influence on their children glycemic control.…”
Section: Discussioncontrasting
confidence: 36%
“…In our society mothers usually combine their children during visits to pediatric diabetes clinic, where they receive an intensive program conducted by diabetic health team with each visit to clinic, while most of the time fathers don't attend to clinic and depends on mother's knowledge of diabetes. According to a study of the family interaction in pediatric diabetes in 2011, it showed that fathers almost don't step to help mothers in the management plan until glycemic control begins to deteriorate, for this reason it suggests and encourages father's active Turkish study in 2010 involved 93 diabetic participants, found significant higher HbA1c among children of lower educated fathers (p=0.02) than in children of more educated fathers, however, there was no such relation between mothers' educational level and their children HbA1c (p=0.31) [13]. This study has supported the influence of both fathers' educational level and occupational status on glycemic control of children with TIDM, which has as well supported by other study, but no significant influence of mothers' educational level and occupational status was found [13].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The sample size range is 70 to 30 708 patients with a median sample size of 210 T1D patients. Thirty‐two studies were performed in several European countries, 31 in USA, one in Canada, three in Israel, and the rest in other countries (one in Japan, one in New‐Zealand, three in Turkey, one in Australia, and three are multinational). Most studies (54 studies) were performed on T1D children (median of mean age reported in articles 12.5 [range: 4.1‐17.7]), 22 included both children and young adults (median of mean age of 14.8 [range: 10.1‐21.6]), and one included only young adults (mean age of 19.4 ± 0.9 [range: 18‐21]).…”
Section: Resultsmentioning
confidence: 99%
“…In general, adolescents have worse glycemic control compared to younger children, and girls tend to have poorer glycemic control compared to boys [11]. Studies have also shown a correlation between parental educational level and the outcome of the child's glycemic control [12][13][14].…”
mentioning
confidence: 99%